Gearbox condition monitoring in wind turbines: A review. (October 2018) - Salameh, Jack P.; Cauet, Sebastien; Etien, Erik; Sakout, Anas; Rambault, Laurent
Highlights: New advances in lubrication analysis, vibration analysis, and electrical analysis of wind turbines. Advances in SCADA data application for gearbox fault detection. Advances in MCSA application for gearbox fault detection. Abstract: Wind turbine technology is experiencing rapid growth with respect to size, market share, and technological design. Operational and maintenance cost directly determine whether the system is efficient in terms of energy production in comparison with other types of power plants. Condition monitoring of wind turbines is the major field of studies in recent years aiming to increase lifetime expectancy of components while reducing operation and maintenance cost. Operators and researchers are focusing on improving fault detection techniques in order to render wind turbines more reliable. Gearbox in wind turbines has the greatest share of downtime among all other components affecting directly the cost of operation and maintenance. This paper gathers a review on different methods and techniques for gearbox condition monitoring in wind turbines. Furthermore, various methods and techniques in the literature will be presented in order to get an insight onto the most used methods in wind turbine gearbox condition monitoring. Challenges and future aims are also discussed to determine the focus of condition monitoring systems.